Organic Non‐Wettable Superhydrophobic Fullerite Films. Issue 32 (17th June 2021) - Saran, Rinku; Fox, David; Zhai, Lei; Chanda, Debashis
Abstract: A long‐standing quest in material science has been the development of non‐wettable superhydrophobic films based on a single organic material, without the requirement of fluorination or silane treatment. Here, such films and coatings, which are developed using colloidal gels of fullerite C60 and C70 nanocrystals, are described. It is illustrated that despite the high surface energy of these van der Waals molecular crystals their gelation can create films having self‐affine fractal surfaces with multiscale roughness. Water droplets on resulting surfaces of fullerite films bead like a pearl resting in a Fakir state with contact angle exceeding 150°. The films are extremely water repellent and non‐wettable; when submerged in water they stay dry up to 3 h even at a water depth of two feet and exhibit the plastron effect. A series of experiments are presented to provide comprehensive inspection of water droplet dynamics on these films. These include rolling, bouncing, squeezing, freezing, melting, evaporating; along with acidic and alkaline tests. Non‐wettable films of such materials are unique as fullerites get photosensitized instantaneously generating extremely high yields (≈100%) of singlet oxygen ( 1 O2 ) that can destroy viruses and bacteria; thereby enabling their use in rheology, water purification, and medicinal devices. Abstract : Solubility and wettability of solids signify their interaction with liquids. The findings on fullerites—the only soluble form of pure carbon—are presented. It is demonstrated that solution‐cast fullerite films developed from colloidal gels generate a non‐wettable superhydrophobic surface. They can be used directly in a plethora of practical applications requiring ultra‐hydrophobicity and underwater photochemical applications.